1983
DOI: 10.1128/mcb.3.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Altered cell spreading in cytochalasin B: a possible role for intermediate filaments.

Abstract: Trypsinized chicken embryo dermal fibroblasts plated in the presence of cytochalasin B (CB) quickly attached to the substrate and within 24 h obtained an arborized morphology. This morphology is the result of the pushing out of pseudopodial processes along the substrate from the round central cell body. There were no microfilament bundles in the processes of these cells plated in the presence of CB; however, the processes were packed with highly oriented, parallelaligned intermediate filaments. Rous sarcoma vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…However, the resultant morphology was clearly different from that produced by tumor promoters. The colonies remained in tight clusters; although there was a partial breakdown of intercellular association (25), the major characteristics of changes induced by tumor promoters (i.e., rapid cell spreading and the formation of long, cytokeratin-rich filament bundles) were not observed in response to cytochalasin D. When TPA was added to MDCK colonies previously exposed to cytochalasin D (Fig. 5d), both cell spreading and process formation were observed.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the resultant morphology was clearly different from that produced by tumor promoters. The colonies remained in tight clusters; although there was a partial breakdown of intercellular association (25), the major characteristics of changes induced by tumor promoters (i.e., rapid cell spreading and the formation of long, cytokeratin-rich filament bundles) were not observed in response to cytochalasin D. When TPA was added to MDCK colonies previously exposed to cytochalasin D (Fig. 5d), both cell spreading and process formation were observed.…”
Section: Resultsmentioning
confidence: 95%
“…4. Five structurally unrelated compounds, all known to be complete or secondstage tumor promoters (19,(22)(23)(24), are shown to induce iden- (25). When TPA at 5 ng/ml was added for 2 hr to cells previously treated with colchicine (b), the cytokeratin pattern observed was characteristic of cells treated with TPA alone (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies have demonstrated cytochalasin effects on cellular adhesion and/or cell spreading (52)(53)(54)(55)(56)(57)(58). In addition, several groups have demonstrated an intact focal adhesion signaling pathway in 293 cells and its sensitivity to cytochalasin D (59 -61).…”
Section: Discussionmentioning
confidence: 99%
“…These neurites tended to have round tips and loop shapes like those continuously exposed to the drug (13). Cytochalasin B may inhibit the addition of actin subunits to the lengthening end of the actin filament (8,12,14). The control and our experimental cell cultures that had been extracted by the tetrahydrofuran method, respectively, contained 6.58 nmoles and 4.68 nmoles of total ganglioside-sialic acid per mg cell protein (Table 1).…”
Section: Methodsmentioning
confidence: 99%